2018
DOI: 10.3390/ijms19092765
|View full text |Cite
|
Sign up to set email alerts
|

TOP2B: The First Thirty Years

Abstract: Type II DNA topoisomerases (EC 5.99.1.3) are enzymes that catalyse topological changes in DNA in an ATP dependent manner. Strand passage reactions involve passing one double stranded DNA duplex (transported helix) through a transient enzyme-bridged break in another (gated helix). This activity is required for a range of cellular processes including transcription. Vertebrates have two isoforms: topoisomerase IIα and β. Topoisomerase IIβ was first reported in 1987. Here we review the research on DNA topoisomeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 152 publications
(198 reference statements)
3
94
0
Order By: Relevance
“…The major contribution of TOP2A protein in PDS-dependent induced DNA breaks appears slightly surprising as a major role on transcription has been credited to TOP2B isoform (20,26,27,70). In human cells, TOP2A is highly expressed in proliferating cells, and further upregulated during S and G2 phases where it plays an essential role during replication and chromosome segregation (20,26,45,46).…”
Section: Discussionmentioning
confidence: 99%
“…The major contribution of TOP2A protein in PDS-dependent induced DNA breaks appears slightly surprising as a major role on transcription has been credited to TOP2B isoform (20,26,27,70). In human cells, TOP2A is highly expressed in proliferating cells, and further upregulated during S and G2 phases where it plays an essential role during replication and chromosome segregation (20,26,45,46).…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that CC-seq maps CCs of both human TOP2α and TOP2β-452 proteins that are conserved amongst all vertebrates and whose functional differences453 remain a subject of interest within the field(Austin et al, 2018). Given the essential 454 requirement for TOP2α during mitosis(Akimitsu et al, 2003), and the apparent inability of 455 TOP2β to compensate for its loss(Grue et al, 1998), it will be particularly interesting to456 determine the genomic distribution of TOP2α/TOP2β activities throughout the cell cycle,457 and to relate this to 3D chromatin conformation measured by Hi-C. Whilst not essential for458 cell proliferation, TOP2β plays an important role in promoting transcriptional programmes 459 associated with neuronal development (Tiwari et al, 2012), and this function cannot be 460 supported by TOP2α.…”
mentioning
confidence: 99%
“…Subsequently, glucocorticoid receptor was also reported to transactivate genes via TOP2β-produced DSBs [73]. Additionally, TOP2β is expressed in differentiation cells and neurons [74,75]; the expression of long-transcripts linked to autism is facilitated by TOP2β [76]. While it is indeed intriguing for an essential role of DSBs at least in a subset of gene transcription, it is clear that DSBs need to be effectively repaired regardless of their sources of generation owning to their toxic impact on genome stability [77].…”
Section: Link Of Dsb With Admentioning
confidence: 99%